2010
DOI: 10.1542/peds.2010-2005
|View full text |Cite
|
Sign up to set email alerts
|

Sport-Related Concussion in Children and Adolescents

Abstract: Sport-related concussion is a "hot topic" in the media and in medicine. It is a common injury that is likely underreported by pediatric and adolescent athletes. Football has the highest incidence of concussion, but girls have higher concussion rates than boys do in similar sports. A clear understanding of the definition, signs, and symptoms of concussion is necessary to recognize it and rule out more severe intracranial injury. Concussion can cause symptoms that interfere with school, social and family relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
445
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 581 publications
(455 citation statements)
references
References 129 publications
4
445
2
1
Order By: Relevance
“…A large part of these diseases is closely connected with level of resistance; this allows concluding that implementing Wellness events have nonspecific effects on children and adolescents, increasing the resistance to the body. [5][6][7] In the study of the incidence of investigated contingent identified some features that you should pay attention to when medical control of these contingents:…”
Section: Discussionmentioning
confidence: 99%
“…A large part of these diseases is closely connected with level of resistance; this allows concluding that implementing Wellness events have nonspecific effects on children and adolescents, increasing the resistance to the body. [5][6][7] In the study of the incidence of investigated contingent identified some features that you should pay attention to when medical control of these contingents:…”
Section: Discussionmentioning
confidence: 99%
“…Defining the pathophysiology of pediatric SRC is paramount, given the high incidence of this injury, [1][2][3][4][5][6]40 considerable recent lay press attention, and the potential for short-and long-term impact on health and well-being. 13,16,[41][42][43][44][45][46][47] To study similarities and differences between pediatric and adult SRC, we evaluated a small cohort of children with SRC and healthy controls, using ImPACT neurocognitive testing and MRI measures of brain structure, metabolism, organization, and blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Despite its high incidence, the pathophysiology of SRC is not well understood. Symptoms and neuropsychological alterations of SRC have been well characterized [8][9][10][11][12][13][14][15][16][17][18][19] ; however, the biological substrate has been studied limitedly, largely in adults and focusing on structural injury patterns.…”
mentioning
confidence: 99%
“…Improve medical education about concussion. This includes better concussion education for students entering health professions but also improved education for health care professionals after graduation [10,11]. A study found that only 26.6 percent of general pediatricians were somewhat or very familiar with recently passed concussion legislation and that only 14.6 percent of general pediatricians used concussion consensus guidelines in their practice [12].…”
Section: Recommendationsmentioning
confidence: 99%